Continuous N2O and CO2 fluxes by Eddy Covariance technique on a shallow drained agricultural boreal peatland ... - Gerin, Stephanie; Vekuri, Henriikka; Liimatainen, Maarit; Tuovinen, Juha-Pekka; Kekkonen, Jarkko; Kulmala, Liisa; Laurila, Tuomas; Linkosalmi, Maiju; Liski, Jari; Joki-Tokola, Erkki; Lohila, Annalea (Finnish Meteorological Institute, 2023)
This package contains data from a drained agricultural boreal peatland for grass silage in Northern Finland. The field, located in Ruukki (N64°41.039' E25°6.379'), has a shallow peat depth of 15-30cm. Eddy-covariance measurements cover the period 5th of November 2019 to 31st December 2021. EC_CO2_fluxes.csv contains the gapfilled 30-min mean CO2 fluxes (NEE) and its components (GPP and respiration). EC_N2O_fluxes_v2.csv contains the ungapfilled 30-min mean N2O fluxes, friction velocity and limit of detection. Metadata.csv contains the 30-min means of meteorological and soil variables from the site. Daily_precipitation.csv contains the daily sums of precipitation. Field_management.csv contains information on field management events (fertilization, harvest etc.). ...